Intra-arterial analysis of the best calibration methods to estimate aortic blood pressure. Issue 2 (February 2019) - Picone, Dean S.; Schultz, Martin G.; Peng, Xiaoqing; Black, J. Andrew; Dwyer, Nathan; Roberts-Thomson, Philip; Qasem, Ahmad; Sharman, James E.
Abstract : Objective: Estimation of aortic blood pressure (BP) requires peripheral BP waveform calibration. Mean arterial pressure (MAP)/DBP calibration is purported to estimate aortic BP more accurately than SBP/DBP calibration. However, this is based on inaccurate cuff calibration. Thus, direct comparisons of each calibration method using intra-arterial BP are required to confirm this, and was the aim of this study. Methods: Ascending aortic, brachial and radial artery intra-arterial BPs were measured among 107 patients (61.9 ± 10.0 years, 70% men) undergoing coronary angiography. Radial waveforms were calibrated with brachial SBP/DBP and brachial MAP/DBP to directly test the accuracy of estimated aortic SBP (derived using a commercial device) from each calibration compared with intra-arterial aortic SBP. Estimated aortic BP accuracy from aortic MAP/DBP, brachial and radial SBP/DBP calibrations of peripheral waveforms was also tested (six calibration methods in total; all using intra-arterial BP). Results: Estimated aortic SBP from brachial MAP/DBP calibration of radial waveforms had a significantly smaller mean difference than from brachial SBP/DBP calibration (−0.7 ± 7.5 mmHg versus −6.9 ± 7.3 mmHg, P < 0.0001 for difference). Of the other calibration methods, estimated aortic SBP was most accurate from aortic MAP/DBP calibration of radial waveforms (−1.8 ± 5.0 mmHg, P = 0.00023). However, for all calibration methods, aortic-to-brachial artery and/or brachial-to-radial artery SBP amplification had a major influence on estimated aortic SBP. Conclusion: Brachial and aortic MAP/DBP were confirmed as the best calibration methods to estimate aortic SBP, but irrespective of calibration method, accuracy was significantly influenced by the level of SBP amplification. Thus, improved accuracy of estimated aortic SBP should be possible by closer consideration of SBP amplification or individual waveform characteristics that differ according to the level of SBP amplification. Abstract : Supplemental Digital Content is available in the text